Security Risks in Remote Work Infrastructure: Analysis of VPN Vulnerabilities and Insider Threats - Haq, Syed Mazhar Ul (International Journal of Research in Interdisciplinary Studies, 2025)
The widespread adoption of remote work following the COVID-19 pandemic has significantly transformed enterprise network infrastructures. Organizations increasingly rely on Virtual Private Networks (VPNs) and remote desktop technologies to enable secure access to corporate resources from off-site locations. However, this shift has simultaneously introduced critical security risks, particularly when such tools are misconfigured, poorly monitored, or targeted by sophisticated cyberattacks. Additionally, the emergence of insider threats—authorized users who intentionally or unintentionally compromise network security—poses a persistent and often underestimated challenge. This study explores the security risks associated with remote work infrastructure by examining vulnerabilities in VPN deployment and analysing the dynamics of insider threats. Simulation models and real-world incident data are leveraged to highlight risk vectors and mitigation strategies. Findings show a direct correlation between VPN mismanagement and data breaches, with insider activity contributing significantly to incident response failures. The study proposes an integrated framework combining Zero Trust Network Access (ZTNA), continuous monitoring, and user behaviour analytics (UBA) to enhance remote work security resilience.